Effects of Bifidobacteria Fermentation on Physico-Chemical, Thermal and Structural Properties of Wheat Starch - Hong, Jing; Guo, Wanxue; Chen, Peixia; Liu, Chong; Wei, Juan; Zheng, Xueling; Saeed Omer, Saeed Hamid (Foods, 2022)
Lactic acid bacteria have been considered to be a very important species during sourdough fermentation. In order to explore the effects of bifidobacteria fermentation on thermal, physico-chemical and structural properties of wheat starch during dough fermentation, starch granules were separated from the fermented dough at different fermentation times, including 0 h, 2 h, 6 h, 9 h and 12 h. The results showed that the morphology of starch granules was destroyed gradually as the fermentation time increased, which appeared as erosion and rupture. With the increase in fermentation time, the solubility showed a significant increase, which changed from 8.51% (0 h) to 9.80% (12 h), and the swelling power was also increased from 9.31% (0 h) to 10.54% (12 h). As for the gelatinization property, the enthalpy was increased from 6.77 J/g (0 h) to 7.56 J/g (12 h), indicating a more stable thermal property of fermented starch, especially for the longer fermentation. The setback value was decreased with short fermentation time, indicating that the starch with a longer fermentation time was difficult to retrograde. The hardness of the gel texture was decreased significantly from 50.11 g to 38.66 g after fermentation for 12 h. The results show that bifidobacteria fermentation is an effective biological modification method of wheat starch for further applications.